Come dovranno essere i medici del prossimo futuro?. Issue 2 (June 2018) - Antonio, Barracca; Patricelli, Patrizia Francesca; Rinaldi, Maria Rosa; Quintaliani, Giuseppe
How should doctors be in the near future? The history of man and that of medicine are a compendium that links the past to the present with one main difference: the past has been characterized by a slow progression of the medical sciences that has necessarily taken long time to establish a solid foundation for our knowledge; instead, the present is characterized by a fast-paced progress of knowledge that uses innovative tools and methods. In the past, progress and knowledge have been linked to revolutionary scientists who, alone, anticipated and imagined the future. In the present, knowledge and progress are the result of large organizations, Universities, biotechnology laboratories, and the ability to study big data. But at the basis of medical training remain logical knowledge, probabilistic reasoning, in-depth study of the functioning of the human body and its alterations. Both past and present must always coexist in a doctor's culture.